Effects of Enterprise Resource Planning (ERP) on the Financial Performance of WADE Funeral Services - Wadesango, Newman; Karaga , Clemence; Sitsha, Lovemore (The Journal of Accounting and Management, 2024)
The research sought to determine the effects of enterprise resource planning (ERP) on the financial performance of WADE Funeral Services. Furthermore, those charged with the governance of WADE Funeral Company averred that the rampant changes in the digital environment with the introduction of Artificial intelligence, (AI), internet of things (IOT) and crypto services such as block chains is compromising the effectiveness of ERPs. The entity has been facing financial woes as it strives to keep pace with system upgrade costs, system updates, system maintenance and training costs. The financial performance of the entity has reached a milestone between the past 3 successive years from 2020 to 2022 as far as decreasing financial trajectories are concerned. The study adopted a mixed research approach. Data were collected using questionnaires and interviews. The study targeted 73 participants working at WADE Funeral Company’s head offices. It emerged that Adopting ERP affects the financial performance of WADE Funeral Company. Enterprise resource planning helps to corroborate resources and effectively optimize data management thereby improving the performance of corporate entities. WADE Funeral Company does not have the requisite technological infrastructure so embracing ERP can expose these firms to marginal costs. ERP help in streamlining administration and automating resource management, through ERP help to enhance efficiency and effectiveness. WADE Funeral Company is struggling to embrace and harness proceeds of ERP software due to political interference, economic oscillations, legal regulations, technological dynamism, illiteracy levels and poor management and leadership styles. There is a raft of factors which affects the implementation of ERPs in funeral services companies, and these can be internal or external factors.